KEPEMIMPINAN YANG BERSAHABAT: KAJIAN PELAYANAN KEPEMIMPINAN INTEGRASIONAL DALAM MENJAWAB TANTANGAN PELAYANAN BERGEREJA DI INDONESIA - Mofun, Costantinus Ponsius Yogie (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2024)
In various churches in Indonesia, there are still not too many intergenerational patterns of ministry. This is because in the church system the relationship between generations is not very strong. There are several generations that have always dominated in it and caused other generations to not be actively involved in the church. The process also takes place within the leadership of the church. Leadership in the church in Indonesia has always placed their position as servitude leadership. This is seen from the concept of understanding that church leaders are servants of God. This servitude leadership is also often seen as leadership that is done with the dominant thing so that the ministry cannot run effectively. Therefore, friendly leadership is needed in answering the problems that occur.